Pattern of Biopsy Gleason Grade Group 5 (4 + 5 vs 5 + 4 vs 5 + 5) Predicts Survival After Radical Prostatectomy or External Beam Radiation Therapy - Wenzel, Mike; Würnschimmel, Christoph; Chierigo, Francesco; Mori, Keiichiro; Tian, Zhe; Terrone, Carlo; Shariat, Shahrokh F; Saad, Fred; Tilki, Derya; Graefen, Markus; Mandel, Philipp; Roos, Frederik C; et al. (European urology focus, 2022)
BACKGROUND: Previous cancer-specific mortality (CSM) analyses for different Gleason patterns in Gleason grade group (GGG) 5 cancer were limited by sample size. OBJECTIVE: To test for differences in CSM according to biopsy GG 5 patterns (4 + 5 vs 5 + 4 vs 5 + 5) among patients undergoing radical prostatectomy (RP) or external beam radiation therapy (EBRT). DESIGN, SETTING, AND PARTICIPANTS: Patients in the Surveillance, Epidemiology and End Results database treated with RP and EBRT (2004-2016) were identified and stratified according to Gleason 4 + 5 versus 5 + 4 versus 5 + 5. INTERVENTION: RP or EBRT. OUTCOME MEASUREMENTS AND STATISTICAL ANALYSES: Kaplan-Meier and multivariable Cox regression models predicting CSM were constructed. RESULTS AND LIMITATIONS: Of 17 263 eligible patients with GG 5 cancer at biopsy (RP: n = 7208; EBRT: n = 10 055), 12 705 had Gleason 4 + 5, 3302 had Gleason 5 + 4, and 1256 had Gleason 5 + 5 disease. Median age, prostate-specific antigen (PSA) at diagnosis, and advanced cT and cN stages significantly differed by Gleason pattern (Gleason 4 + 5 vs 5 + 4 vs 5 + 5; all p < 0.001). The 10-yr CSM rate was 18.2% for Gleason 4 + 5, 28.0% for Gleason 5 + 4, and 39.1% for Gleason 5 + 5 (p < 0.001). In multivariable analyses for the entire cohort adjusted for PSA, age at diagnosis, and cT and cN stage, Gleason 5 + 4 and Gleason 5 + 5 were associated with 1.6- and 2.2-fold higher CSM, respectively, relative to Gleason 4 + 5. In addition, Gleason 5 + 4 and Gleason 5 + 5 were associated with 1.6- and 2.5-fold, and 1.5- and 2.1-fold higher CSM rates in the RP and EBRT subgroups, respectively, relative to Gleason 4 + 5 (all p < 0.001). CONCLUSIONS: For patients with biopsy GG 5 prostate cancer treated with RP or EBRT, there are important CSM differences by Gleason pattern (4 + 5 vs 5 + 4 vs 5 + 5). Ideally, the individual Gleason pattern should be considered in pretreatment risk stratification. PATIENT SUMMARY: For patients with grade 5 prostate cancer, we found differences in cancer-specific death rates according to the pattern of abnormal cells in the prostate, called the Gleason score. The highest death rate was found for a Gleason pattern score of 5 + 5, followed by Gleason 5 + 4 and then Gleason 4 + 5. These differences were observed for both patients who were treated with prostate removal and patients who underwent radiotherapy.
Keywords: Male; Neoplasm Grading; Prostate; biopsie; Prostatic Neoplasms; mužské pohlaví; prostata; Gleason pattern 5; prostatektomie; prostatický specifický antigen; lidé; Gleason sum score; stupeň nádoru; Humans; Prostate cancer; nádory prostaty; Gleason grade group 5; Biopsy; High risk; Prostatectomy; Prostate-Specific Antigen